Cultural Aspects and Their Influence on the Development of Translation Competence (Spanish and Arabic) as a Model - OLA AHMED ABDULRIDHA, Asst. Lecturer (lark, 2026)
Translation is like a ship that sails the seas of languages, transporting ideas and cultures around the world. Every society has its own identity, called culture. Therefore, the relationship between the two is very important, as translation is the only means through which it is possible to understand the cultures of countries that do not speak our language. In our study, we address the concept of translation and its close relationship with culture, as cultural knowledge is considered an essential and indispensable element in the translation process due to its direct influence on conveying meaning accurately and clearly from one language to another. We also highlight the role of the translator as a linguistic and cultural mediator, as well as the characteristics and skills they should possess before undertaking any translation process, such as linguistic competence, cultural awareness, and the ability to analyze and deeply understand texts.